Cancer Stem Cells and Combination Therapies to Eradicate Them - Tang, Qi; Yin, Dan; Wang, Yao; Du, Wenxuan; Qin, Yuhan; Ding, Anni; Li, Hanmei (Current Pharmaceutical Design, 2020)
Cancer stem cells (CSCs) show self-renewal ability and multipotential differentiation, like normal stem or progenitor cells, and which proliferate uncontrollably and can escape the effects of drugs and phagocytosis by immune cells. Traditional monotherapies, such as surgical resection, radiotherapy and chemotherapy, cannot eradicate CSCs, however, combination therapy may be more effective at eliminating CSCs. The present review summarizes the characteristics of CSCs and several promising combination therapies to eradicate them.
Keywords: photothermal therapy